Adsorption removal of zinc (II) from aqueous phase by raw and base modified Eucalyptus sheathiana bark: Kinetics, mechanism and equilibrium study - Afroze, Sharmeen; Sen, Tushar; Ang, Ha Ming (Elsevier, 2016)
In this study, potential application of abundantly available agricultural by-product Eucalyptus sheathiana bark in its raw and sodium hydroxide (NaOH) modified form to remove Zn2+ from its aqueous solutions was investigated by considering parameter identification and optimization, reusability, equilibrium, kinetic and thermodynamic studies. The adsorbent was characterized by SEM-EDX, FTIR, XRD, BET surface area and bulk density and point of zero charge were also determined. The process was strongly pH dependent and the adsorption percentage of Zn2+ was increased with an increase in solution pH from 2.5 to 5.1. Conversely, the adsorption percentage of Zn2+ decreased with the increase in adsorbent dosage, initial metal concentration, temperature and ionic strength. Kinetic measurements showed that the process was multistep, rapid and diffusion controlled. It was found to follow the pseudo-second-order rate equation. Equilibrium adsorption studies showed that both Freundlich and Langmuir models are applicable for both raw and base modified eucalyptus bark. MPSD error function was used to treat the equilibrium data using non-linear optimization technique for evaluating the fit of the isotherm equations. The maximum sorption capacity of modified eucalyptus bark was 250.00 mg/g at 30 °C which was comparative to other adsorbents. Various thermodynamic parameters indicate that the process was spontaneous and physical in nature. Desorption studies were also performed to determine possible recovery potential of Zn2+ and the re-usability of the biomass and to identify the mechanism of adsorption.